Rancang Bangun Sistem Pemesanan Tiket Pada Perum Damri Stasiun Pontianak Berbasis Web dan SMS Gateway - Belang, Paula Putri (Jurusan Informatika Universitas Tanjungpura, 2014)
Nowadays, the Internet has become an important requirement and a major. Internet helps alleviate human tasks in daily life. The Internet can make a system becomes limited by distance, area and time assisted by an extensive network and open for anyone to access it. And in the business world, the internet is also used as a very practical interface for communication between the company and its customers. The purpose of this research is to design and build a web-based ticket booking system that is easier for customers to book tickets, as well as administrative personnel in making financial reports, bus rental, enhancing the efficiency and effectiveness of employee performance that are beneficial to the advancement of the Company of Public Station DAMRI Pontianak. The research method that used is pieces, the method is to identify problems containing an analysis of the performance, information, economy, control, efficiency, and service. Analysis was conducted on the old system, of this analysis will be obtained several problems and finally found the main problem. The results achieved is a web-based ticket booking system that is beneficial to recapitalize the company in booking tickets and bus rental and enable customer in order tickets as well as to regulate the administration report admin. The conclusions of this research, this system is an excellent medium for Company of Public Station DAMRI Pontianak to provide services that make it easier for customers to book bus tickets. Test results on systems built respondents, using Likert's Summated Rating (LSR) method, the measurement results obtained with a score of 2335. Based on the scale of 1800< score <2400, a score of 2335 indicates that the system is built was considered quite successful.